Prevention Of Shwartzman’S Phenomenon In Factor XIII Deficiency - Young Lee, Soo; Keun Chang, Sung; Chung, Soo II (Thrombosis and Haemostasis, 1981)
Cross-linked clots formed in vitro are reported to be more resistant to fibrinolysis but the relevance of these observations to the situation in vivo is uncertain. The possible role of Factor XIII in the formation of diffuse intravascular fibrin deposition was examined in experimentally induced Factor XIII deficient rabbits. Factor XIII deficiency was induced by intravenous infusion of IgG isolated from goat anti-rabbit platelet Factor XIII. Control received normal goat IgG. The Shwartzman reaction was produced by two injections of bacterial endotoxin given 24 hours apart.The most striking histological differences were observed after 48 hours. A large number of glomerular loops were enlarged and engorged with red blood cells and platelet- fibrin thrombi; extensive bilateral cortical necrosis was observed in 8 out of 10 endotoxin injected control rabbits but none in the Factor XIII deficient group.Fibrinogen levels in control rabbits were increased 3-4 fold (1.1g/100 ml), at 24 hours and slightly decreased at 48 hours after endotoxin injection, whereas in Factor XIII deficient animals, the rate of increase was slower but reached similar levels at 48 hours. Fibrinolytic activity in vivo, studied by the degradation of infused 125I-fibrinogen, was significantly increased in both endotoxin injected groups, irrespective of Factor XIII levels.These results strongly suggest that cross-linked thrombi are more resistant to fibrinolysis in vivo as well as in vitro.